Estimating carbon fluxes in a Posidonia oceanica system: Paradox of the bacterial carbon demand. (20th March 2016) - Velimirov, B.; Lejeune, P.; Kirschner, A.; Jousseaume, M.; Abadie, A.; Pête, D.; Dauby, P.; Richir, J.; Gobert, S.
Abstract: A mass balance ecosystemic approach, based on bacterial carbon demands and primary production data, was used to investigate if the bacterial community (freewater bacterioplankton and benthic bacteria of the oxygenated sediment layer) could be sustained by the main primary producers ( Posidonia oceanica and its epiphytes, adjacent macroalgae and phytoplankton communities; hereafter called the P. oceanica system) of a non-eutrophic Mediterranean bay. Unexpectedly, the findings of this study differed from previous works that used benthic incubation chamber and O2 optode methods. In this study, data were grouped in two categories, corresponding to two time periods, according to the seawater temperature regime (<18 °C or >18 °C): from May to October and from November to April. Between May and October, the produced benthic macrophyte tissues could not provide the carbon required by the bacteria of the oxygenated sediment layer, showing that the balance production of the investigated bay was clearly heterotrophic ( i.e . negative) during this time period. In contrast, between November and April, benthic bacteria respiration nearly equated to carbon production. When integrating the open water carbon dynamics above the meadow in the model, a negative carbon balance was still observed between May and October, while a slight carbon excess was noticed between November and April. In the light of these findings, the carbon balance being negative on an annual basis, alternative carbon sources are required for the maintenance of the bacterial carbon production. Highlights: An ecosystemic approach of carbon balance in a Posidonia oceanica system was chosen. Data from 40 years of scientific investigations were compiled. The annual carbon balance between bacteria and primary producers is negative. Alternative carbon sources are necessary to sustain the bacterial production.